Urban spaces : plazas, squares and streetscapes - Uffelen, Chris van. (Salenstein : Braun Publishing Inc., 2013)
Public urban spaces vary widely in type, form and size, encompassing plazas, squares and streetscapes. They serve pedestrians and flaneurs, accommodate street life in all its vibrant variations and represent the cities and towns themselves. On the one hand they are transit spaces or crossroads, while on the other hand they provide opportunities to linger or stage events. This volume features recent projects from all continents, showing the different approaches and solutions to this sophisticated design task at the intersection of architecture, landscape design and urban planning. Hardly any other area of spatial design offers such functional and formal diversity as does the design of urban spaces.
Preface -- Forum -- Theatron -- Corso -- Architect's index -- Picture credits -- Imprint.
Includes index.
Keywords: PUBLIC SPACES -- PICTORIAL WORKS